2006
DOI: 10.1002/star.200600528
|View full text |Cite
|
Sign up to set email alerts
|

An Aqueous Film‐coating Formulation based on Sodium Carboxymethyl Mungbean Starch

Abstract: No abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…Previously, it was reported that preparing carboxymethyl cocoyam starch at 70 O C caused starch gelatinization [13]. Increase in the DS with temperature as observed here is consistent with the carboxymethylation of mungbean starch [7].…”
Section: Effect Of Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, it was reported that preparing carboxymethyl cocoyam starch at 70 O C caused starch gelatinization [13]. Increase in the DS with temperature as observed here is consistent with the carboxymethylation of mungbean starch [7].…”
Section: Effect Of Temperaturesupporting
confidence: 91%
“…Applications in food [1,2] environmental management [3][4][5], agriculture [6], pharmacy [7], biomedical engineering [8] and textile [9] have been reported widely in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxymethyl starch is cold water soluble material giving viscous, colourless and transparent solutions. It could be applied in food, medicine, pharmacy 60, textile 61 and paper sizing, printing, electrodes, ceramics (http://www.modifiedstarchproducts.com/), drilling fluids 62, as corrosion inhibitors 63 or electrorheological fluids 55, 59. However, they mostly correspond to CMS of low DS (below 0.4), as mainly such products are commercially available.…”
Section: Application Of Carboxymethyl Starchmentioning
confidence: 99%
“…In addition to cellulose, polysaccharides such as starch (Kittipongpatana, Chaichanasak, et al, 2006), inulin (Verraest, Peters, Batelaan, & van Bekkum, 1995), and xylan (Petzold, Schwikal, & Heinze, 2006) have also been successfully carboxymethylated. However, the reaction conditions for the carboxymethylation process vary among different types of polysaccharides, and thus it was pertinent to optimize the carboxymethylation process specifically for carrageenan.…”
Section: Introductionmentioning
confidence: 98%